Career patterns within men`s and women`s soccer talent systems: the typical pathway to the top is atypical - Verbeek, J.; Niessen, A. S. M.; Van der Steen, S.; Van Yperen, N. W.; Den Hartigh, R. J. R. (International Journal of Performance Analysis in Sport, 2026)
Talent systems in soccer aim to identify and recruit the most promising players, ideally during early childhood. Compared to non-recruited players, recruited players are typically provided with higher-quality coaching and training facilities, which are assumed to accelerate their skill development. As a result, future elite players are expected to emerge from this group of early recruits in a singular, uninterrupted progression. While recent research increasingly challenges this assumption, how youth players develop within soccer talent systems remains largely unknown. Therefore, this study aimed to examine whether early recruitment correlates with senior performance levels and, as a next step, to quantitatively explore the shape of nearly 3,000 Dutch male and female youth soccer players` career patterns. Results showed that roughly 8% and 10% of all recruited players attained senior elite soccer. In addition, we found a weak relationship between academy recruitment age and the attainment of elite soccer status. More importantly, using Guttman errors to quantify the typicality of career patterns, we discovered that career interruptions were positively related to attaining senior elite soccer status. Specifically, senior international players exhibited diverse and interrupted career patterns. We therefore conclude that the typical pathway to future soccer success can be characterised as atypical.